Quality of Service (QoS) Analysis of Campus Internet Networks: A Case Study at Universitas Islam Sumatera Utara - Satria Yudha Prayogi; Delisman Hulu (The IJICS (International Journal of Informatics and Computer Science), 2025)
The increasing reliance on internet connectivity in higher education institutions requires campus networks to deliver reliable and high-quality services to support academic and administrative activities. However, high user density and traffic load often cause performance degradation, particularly during peak usage periods. This study aims to analyze the Quality of Service (QoS) performance of the campus internet network at Universitas Islam Sumatera Utara to determine whether the existing network infrastructure meets acceptable service quality standards. The research employs a quantitative descriptive approach by measuring key QoS parameters, including throughput, delay, packet loss, and jitter, under peak and non-peak usage conditions. Network performance data were collected through direct measurement and analyzed based on TIPHON and ITU-T standards. The results indicate that network performance degrades during peak hours due to increased traffic load, resulting in lower throughput and higher delay, packet loss, and jitter. Nevertheless, all measured parameters remain within acceptable QoS thresholds, indicating that the campus network is generally capable of supporting academic, administrative, and online learning activities. This study provides valuable insights into campus network performance and highlights the importance of bandwidth management and continuous QoS monitoring to maintain service quality as user demand increases